Overview of Pakistan’s Transportation Infrastructure from Future Perspective: A Systematic Literature Review - Khan, Muhammad Rahies; Suleman Aziz; Rao Muhammad Rashid; Azmat Ullah Baig (Journal of Applied Research and Multidisciplinary Studies, 2024)
Economic growth has emerged as the most influential tool in the recent years and an efficient transport infrastructure is one of the key factors to achieve economic development. Furthermore, the integration of advanced technological trends may accelerate the economic activities. However, the same has not been widely discussed in the Pakistani context so far. Therefore, the current study aimed to analyze the existing situation, difficulties, and future prospects for transport infrastructure development in Pakistan. The study investigated significant issues pertaining to the condition of roads, railways, airports, and ports as well as future trends and recommendations along with strategies for sustainable and efficient infrastructure. A systematic literature review was conducted to identify the current state and key opportunities for the development of Pakistan’s transportation infrastructure from future perspective. Findings showed that securing funds, increasing governance and institutional capacity, tackling urban congestion, limiting environmental impacts, and assuring infrastructure maintenance are all difficult tasks. However, the analysis offered opportunities arising from Pakistan’s strategic location, prospects for regional integration, public-private partnerships, technical breakthroughs, tourism, and economic growth. Strategies and recommendations were also provided for policymakers and key stakeholders. Implications concentrated on evaluating active initiatives, conducting region-specific analyses, analyzing the impact, developing creative financing approaches, and integrating the emerging technologies. Pakistan may foster a robust and sustainable transport infrastructure by tackling issues and capitalizing on opportunities, hence boosting economic growth, connectivity, and overall development